FACTORES ASOCIADOS A LETALIDAD POR COVID-19 EN UN HOSPITAL DE LA REGIÓN CAJAMARCA EN PERÚ. - Anyaypoma-Ocón, W. (2021)
Objective. To identify the clinical and epidemiological characteristics related to lethality in patients hospitalized for COVID-19 at the Simón Bolívar Hospital in Cajamarca, during June-August 2020. Materials and Methods. This was a retrospective cohort, that used information collected from clinical records and official epidemiological surveillance systems (NOTIWEB, SISCOVID and SINADEF), on hospitalized patients with confirmed COVID-19 diagnosis. Information was collected on sociodemographic and clinical factors, considering discharge (death/survival) and days of hospitalization as outcomes. Results. The in-hospital fatality rate was 39.6%, and significant differences were found between hospitalization time and status at discharge in people over 60 years of age (p<0.001). Age older than 60 years (HR: 2.87; 95% CI: 1.76-4.68),) unattended ICU bed request (HR: 3.49; 95% CI: 2.02-6.05), oxygen saturation less than 80% at admission (HR: 2.73; 95% CI: 1.35-5.53) and the use of ivermectin (HR: 1.68; 95%CI 1.06-2.68) were factors associated with lethality. The chosen ML model considered that the most important variables were oxygen saturation, age over 60 years, time of hospitalization and time of the onset of symptoms. Conclusion. The factors that could increase lethality in patients hospitalized for COVID-19 were age, oxygen saturation less than 80%, use of ivermectin as part of hospital treatment and unattended request for ICU beds. Future studies with better representativeness could confirm these possible relationships at the regional or national level.